Associations between protein intake status and the association of “double burden of malnutrition” in children aged 2–5 years: a health and nutrition survey of selected children in Bengbu City, China - Zhu, Tongying; Zhang, Li; Li, Rongrong; Li, Xiaoqing; Zhu, Hao; Shu, Li (Frontiers in Nutrition, 2025)
BackgroundProtein intake is widely recognized as a reliable marker for assessing malnutrition. The double burden of malnutrition (DBM) is characterized by the coexistence of malnutrition and overweight, obesity, or diet-related noncommunicable diseases in individuals, families, and populations throughout the life course.MethodsChildren were categorized into quartiles based on the protein index. World Health Organization (WHO) Anthro software was used to assess child growth and development, enabling the prediction of DBM prevalence. Nutrient intake, the effect on DBM were assessed using both a multifactorial logistic regression model and a binary logistic regression correction model.ResultsThe prevalence of DBM increased with higher protein index quartiles. In the regression model, the risk of DBM was significantly higher in the second (Q2) and fourth (Q4) quartiles for both boys (Q2: 1.934, 95% CI: 1.210–3.091; Q4: 1.653, 95% CI: 1.016–2.687) as well as in the girls (Q2: 1.963, 95% CI: 1.263–3.052; Q4: 1.366, 95% CI: 0.857–2.178). In the multivariate models, the association between the protein index and DBM risk persisted as significant even after adjusting for confounding factors.ConclusionThis study revealed a strong correlation between the protein index and DBM prevalence in preschool children aged 2–5 years.